دور وانعكاسات ممارسة الأنشطة البدنية الرياضية الترويحية لفئة المسنين - غربي, أم كلثوم (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية لمعرفة دور ممارسة الأنشطة البدنية الرياضية الترويحية علي فئة المسنين ، من خلال الانعكاسات النفسية والاجتماعية الناجمة عن ممارسة الأنشطة البدنية الرياضية الترويحية للمسنين ، قوامها 20 مسن ممارس ومن ثم معرفة العلاقة بين الأنشطة البدنية الرياضية الترويحية والانعكاسات علي فئة المسنين وكذا معرفة أهمية الأنشطة الترويحية . وقد أظهرت النتائج علي أن النشاط البدني الرياضي الترويحي وسيلة فعالة في تحقيق التوازن الانفعالي والعقلي واسترجاع الثقة في النفس وكذا يخفف من حدة الاكتئاب والحزن والوحدة ، كما يجعل الأشخاص المسنين عند ممارسة الأنشطة البدنية الرياضية الترويحية بشكل متكامل ومنسق من خلال عمليات الاندماج الاجتماعي ، كما يساعد في توسيع الحيز الاجتماعي وخلق علاقات بينهم من خلال التعاون وتحسين المزاج والشعور بالرضا . Abstract: The purpose of the present study is to identify the role of recreational physical activity in the elderly category, through the psychosocial repercussions of recreational physical activities for the elderly, consisting of 20 practicing elderly, and thus the relationship between recreational physical activities and the repercussions on the elderly group, as well as the importance of recreational activities. Results have shown that recreational physical activity is an effective means of achieving emotional and mental balance and restoring self-confidence as well as alleviating depression, sadness and loneliness and makes older persons in the exercise of recreational physical activities in an integrated and coordinated manner through social integration processes, It also helps to expand social space and create relationships between them through cooperation, improved mood and sense of satisfaction. Résumé : La présente étude vise à connaître le rôle des activités récréatives physiques dans une catégorie les personnes âgées, par les répercussions psychosociales des activités récréatives physiques pour les personnes âgées, 20 personnes âgées pratiquant et connaissant ainsi la relation entre les activités physiques récréatives et les répercussions sur le groupe de personnes âgées et l’importance des activités récréatives. Les résultats ont montré que l’activité physique récréative est un moyen efficace d’atteindre l’équilibre émotionnel et mental, de rétablir la confiance en soi et d’atténuer la dépression. La tristesse et la solitude et rend les personnes âgées dans l’exercice d’activités physiques récréatives d’une manière intégrée et coordonnée par des processus d’intégration sociale, Il contribue également à élargir l’espace social et de créer des relations entre eux par la coopération, amélioration de l’humeur et du sentiment de satisfaction.
The role and repercussions of physical recreational activities for the elderly group (field study at the level of the leisure and receational forest bushawi)
مقال
Keywords: النشاط البدني الرياضي الترويحي ، فئة المسنين; recreational physical activity, elderly category; sports récréatifs activité physique , catégorie des personnes âgées.